Faktor-Faktor yang Berhubungan dengan Kejadian Obesitas pada Mahasiswa Fakultas Ilmu Kesehatan Universitas Pembangunan Nasional “Veteran” Jakarta: Factors Associated with the Incidence of Obesity among College Students at Fakultas Ilmu Kesehatan Universitas Pembangunan Nasional “Veteran” Jakarta - Rahadian, Fairy Amara; Wahyuningsih, Utami; Simanungkalit, Sintha Fransiske (Amerta Nutrition, 2024)
Background: Obesity is a nutritional issue with an escalating prevalence. Riskesdas 2018 indicates that the adult obesity rate has reached 21,8%. College students are in a transitional phase from adolescence to adulthood, which necessitates adaptation to the academic environment that often lead to the development of unhealthy lifestyles. This issue causes college students susceptible to obesity due to risk factors, such as eating patterns, eating behavior, physical activity, and stress. Objectives: Analyzing factors associated with the incidence of obesity among college students at Fakultas Ilmu Kesehatan Universitas Pembangunan Nasional (FIKES UPN) "Veteran" Jakarta. Methods: Observational analytic research with a cross-sectional design, conducted from February-April 2024, involving 232 respondents. Respondents were selected using the stratified random sampling. Data were obtained using questionnaires and anthropometric measurements then analyzed using the Chi-Square Test. Results: The statistical analysis indicate that the frequency of sweet food consumption has a p-value of 0.111, sweet beverages frequency (p-value=0.733), high-fat food frequency (p-value=0.036), sweet intake (p-value=1.000), high-fat intake (p-value=0.426), fiber intake (p-value=0.819), emotional eating (p-value=0.057), external eating (p-value=0.871), physical activity (p-value=0.271), and stress (p-value=1.000). Conclusions: The frequency of consuming high-fat foods has been significantly associated with obesity among college students. Consequently, students are recommended to be more mindful of the frequency of high-fat foods, such as fast food and fried food, to minimize factors contributing to obesity. In contrast, obesity is not associated with the frequency of sweet foods and beverages consumption, sweet intake, high-fat intake, fiber intake, emotional eating, external eating, physical activity, and stress.